Analisis Pelayanan Pendaftaran Tanah Pertama Kali Pada Kantor Pertanahan Kabupaten Humbang Hasundutan - Andry Sanjaya; Yusniar Lubis; Dumasari Harahap (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
In order to improve the service performance of government agencies, stakeholders must pay attention to the satisfaction of the people they serve. This study aims to determine the level of community satisfaction and then to analyze the level of gap between service performance and community satisfaction with the services of the Land Office. This type of research is descriptive qualitative research, which aims to reveal the problem or situation as it is or based on the existing facts. The results show that the overall quality of land registration services provided by the Land Office of Humbang Hasundutan Regency has not met community satisfaction. The Land Office of Humbang Hasundutan Regency has not yet fully succeeded in providing good service in land registration for the first time. Obstacles in registering land for the first time at the Land Office of Humbang Hasundutan Regency, namely employees are not quick to handle public complaints, there are unscrupulous officers who try to take advantage of the service process, lack of coordination between officers, and slow service processes. For this reason, it is expected to improve the performance of the employees of the Humbang Hasundutan Regency Land Office and can take policies to discipline their employees so that they are timely in land registration services.